2018
DOI: 10.1063/1.5022480
|View full text |Cite
|
Sign up to set email alerts
|

Narrow spectral linewidth in InAs/InP quantum dot distributed feedback lasers

Abstract: FIG. 5. Minimum linewidth as a function of temperature for a commercial QW DFB laser (blue) and an AR/HR QD DFB laser (red).FIG. 6. Calculated spectral linewidth as a function of the drive current for the AR/HR QD DFB laser. The inset shows the temperature dependence of the minimum linewidth at 155 mA. 121102-4Duan et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 28 publications
(31 reference statements)
0
20
0
Order By: Relevance
“…[23] It has been experimentally demonstrated that linewidths of less than 80 kHz can be achieved from 1550 nm InAs/InP QD DFB lasers with a very low reflectivity antireflection coating (AR) on both facets. [35] For ultra-narrow linewidth operation of semiconductor lasers, light coupling with high-Q resonators in external cavities is typically used, in which ultralow loss passive waveguides for mode selection and for cavity length extension are pivotal. [7,36,37] In the tunable laser reported here, the coupled cavities comprise an all-active two-section FP design, which has much higher waveguide loss compared to the typical exter-nal cavity lasers with low loss silicon nitride or Si.…”
Section: Measurement and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[23] It has been experimentally demonstrated that linewidths of less than 80 kHz can be achieved from 1550 nm InAs/InP QD DFB lasers with a very low reflectivity antireflection coating (AR) on both facets. [35] For ultra-narrow linewidth operation of semiconductor lasers, light coupling with high-Q resonators in external cavities is typically used, in which ultralow loss passive waveguides for mode selection and for cavity length extension are pivotal. [7,36,37] In the tunable laser reported here, the coupled cavities comprise an all-active two-section FP design, which has much higher waveguide loss compared to the typical exter-nal cavity lasers with low loss silicon nitride or Si.…”
Section: Measurement and Analysismentioning
confidence: 99%
“…For QD lasers, the α ‐factor is as low as 0.13, which is more than an order of magnitude lower than that of QWs . It has been experimentally demonstrated that linewidths of less than 80 kHz can be achieved from 1550 nm InAs/InP QD DFB lasers with a very low reflectivity antireflection coating (AR) on both facets . For ultra‐narrow linewidth operation of semiconductor lasers, light coupling with high‐Q resonators in external cavities is typically used, in which ultralow loss passive waveguides for mode selection and for cavity length extension are pivotal .…”
Section: Measurement and Analysismentioning
confidence: 99%
“…In 2016, Bjelica et al [1] from the University of Kassel in Germany proposed a high-quality quantum dot laser growth technology, combining it with the traditional DFB grating coupled resonator structure to develop a QD-DFB laser with a laser linewidth of only 10 kHz and an output power of 12 mW. In 2018, the University of Paris-Sacre in France [26] reported a new InAs/InP quantum dot DFB semiconductor laser with low inversion factor and low linewidth enhancement factor for low temperature sensitivity. This laser had a narrow linewidth (160 kHz); its double-sided coating anti-reflection film design improves laser power by 4 mW and inhibits the space hole burning phenomenon.…”
Section: Surface Grating Dfb Semiconductor Lasermentioning
confidence: 99%
“…The integration of multiple optical functions on a microelectronics chip brings many innovative perspectives, along with the possibility to enhance the performance of photonics integrated circuits (PICs). Owing to the atom-like discrete energy levels, quantum dots (QDs) allow producing energy-and cost-efficient devices with outstanding properties such as low threshold current, good temperature stability and narrow linewidth [2,3]. In particular, direct epitaxial growth of GaAs layers onto silicon with InAs QDs as gain media has been proved to be a meaningful solution for inexpensive and monolithically integrated silicon light emitters [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, direct epitaxial growth of GaAs layers onto silicon with InAs QDs as gain media has been proved to be a meaningful solution for inexpensive and monolithically integrated silicon light emitters [4,5]. In semiconductor lasers, the α-factor is a key parameter resulting from the phase-amplitude coupling effect, and driving the spectral linewidth [3], the sensitivity to optical feedback [6,7], the nonlinear dynamics under optical injection [8] and four-wave mixing generation [9]. The α-factor typically describes the coupling between the carrierinduced variation of real and imaginary parts of susceptibility and is defined as […”
Section: Introductionmentioning
confidence: 99%